Current State of the Art in Cysticercosis and Neurocysticercosis (IntechOpen, 2023)
This book provides updated information to scientists and clinicians on taeniosis/cysticercosis, a parasitic infection caused by eating undercooked beef or pork that is a serious health and veterinary problem in many developing countries. It discusses incidence, risk factors, diagnosis, immunology, symptoms, rare manifestations, and advances in treatment including vaccination and novel drug therapies.